International network competition - Thomas P. Tangerås; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2014)
We analyse network competition in a market with international calls. National regulatory agencies (NRAs) have incentives to set regulated termination rates above marginal cost to extract rent from international call termination. International network ownership and deregulation are alternatives to combat the incentives of NRAs to distort termination rates. We provide conditions under which each of these policies increase efficiency and aggregate welfare. Our findings provide theoretical support for recent policy initiatives by the European Commission.
Keywords: L51; L96; 330; Cross-border ownership; decentralized regulation; international markets; network competition; telecoms; termination rates